2022
DOI: 10.1002/minf.202100294
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Chemical Context for Buchwald‐Hartwig Coupling Reactions

Abstract: We present machine learning models for predicting the chemical context for Buchwald-Hartwig coupling reactions, i. e., what chemicals to add to the reactants to give a productive reaction. Using reaction data from inhouse electronic lab notebooks, we train two models: one based on single-label data and one based on multi-label data. Both models show excellent top-3 accuracy of approximately 90 %, which suggests strong predictivity. Furthermore, there seems to be an advantage of including multi-label data becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Several concepts can be designed to harness data-driven technology for the purpose of optimizing reaction conditions. Work by Gao et al., 10 Genheden et al, 11 as well as Li and Eastgate 12 used neural networks that predict the success probability for a set of substances in each relevant reagent class. In these approaches, often the accuracy of the top- N most probable predictions is evaluated, which rates if the proposed set of N conditions contains the one that achieved the highest yield.…”
Section: Introductionmentioning
confidence: 99%
“…Several concepts can be designed to harness data-driven technology for the purpose of optimizing reaction conditions. Work by Gao et al., 10 Genheden et al, 11 as well as Li and Eastgate 12 used neural networks that predict the success probability for a set of substances in each relevant reagent class. In these approaches, often the accuracy of the top- N most probable predictions is evaluated, which rates if the proposed set of N conditions contains the one that achieved the highest yield.…”
Section: Introductionmentioning
confidence: 99%
“…Predictive chemistry and reaction informatics is one such field where there have been numerous impressive developments over the past few years despite only a handful of data sets being accessible to researchers, even commercially. Many of these developments are driven by applications of machine learning to, e.g., forward reaction prediction, retrosynthesis planning, and reaction condition prediction where predictions can be made even with relatively small data sets. We and others have asserted that to advance the role of AI in organic synthesis, there must be significant improvements in the reporting of laboratory synthesis procedures, including reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 There are also condition or reagent models suggesting suitable catalysts, solvents, temperatures, etc. 8,9 Finally, there are yield or reactivity models estimating the success of a reaction, which is the topic of this perspective and will be reviewed below. Although many encouraging studies have been reported, ML models for chemistry are not without critique.…”
Section: Introductionmentioning
confidence: 99%
“…Such tools typically fall under the umbrella of computer-assisted synthesis planning and include many different tools and models that can help chemists with several tasks. Retrosynthesis models suggest how to break a compound, either as a single-step prediction or multistep prediction, which provides a sequence of steps for how to synthesize a compound from simpler starting material. Furthermore, there are a range of product prediction models, or forward models that predict what the product of two or more reactants will be, , or can provide guidance on regioselectivity issues. , There are also condition or reagent models suggesting suitable catalysts, solvents, temperatures, etc. , Finally, there are yield or reactivity models estimating the success of a reaction, which is the topic of this perspective and will be reviewed below. Although many encouraging studies have been reported, ML models for chemistry are not without critique. , Furthermore, while many studies emphasize general reaction properties, such as yield prediction in regression and classification tasks, properties tied to physical chemistry, such as reaction rates and activation energies, have received less attention.…”
Section: Introductionmentioning
confidence: 99%